Globalization as a context of resignification of socio-economic and socio-cultural conditions in the Ishamana Community: Wayúu Nation (Encuentros, 2020)
ABSTRACT:The objective of this article is to understand the process of resignification of the pre-post-capitalist socio-economic and socio-cultural conditions of the Ishamana Community: Wayúu Nation, in the context of Globalization. The research is based on the social theory of complexity, from the hermeneutic, explanatory-implicative type, attending to the categories of Agricultural Communism and Common Land Property, Community Organization and Social System, from the point of view of the meanings. In conclusion, ancient and primitive societies, especially the Ishamana Community: Wayúu Nation is for this investigation a territory of Life in which alternative economic, political, social, cultural and human experiences emerge, which resist globalization expansion. Most studies on ancient and primitive societies focus on history, beliefs, language, housing, customs and traditions. This article proposes a hermeneutical perspective from the meanings, on ancient and primitive societies, revealing the emergence of an alternative economic and social system.Keywords: Wayúu Nation, Communism, Collectivism, Globalization. Referencias Castells, Manuel. (2000). “Globalización, sociedad y política en la era de la información”. Revista Bitácora 4-I: 42-53. Castro-Gómez, Santiago y Grosfoguel, Ramón. (2007). En: El giro decolonial: reflexiones para una diversidad epistémica más allá del capitalismo global / compiladores Santiago Castro-Gómez y Ramón Grosfoguel. – Bogotá: Siglo del Hombre Editores; Universidad Central, Instituto de Estudios Sociales Contemporáneos y Pontificia Universidad Javeriana, Instituto Pensar, 2007.Chabod, Federico. (1987). La idea de Nación. México: Fondo de Cultura Económica.De Soussa, Boaventura. (20109. Descolonizar el saber. Montevideo: Ediciones Trilce.De Soussa, Boaventura. (2011). “Introducción: Epistemologías del Sur”. Revista Utopía y Praxis Latinoamericana 16-54: 17-39. De Soussa, Boaventura. (2015). “Construyendo la contrahegemonía: traducción intercultural entre los movimientos sociales”. En: Pensar desde la resistencia anticapitalista y la autonomía, editado por Rafael Sandoval, 27-44. México: Centro de Investigaciones y Estudios Superiores en Antropología Social, Cátedra Jorge Alonso.Deleuze, Gilles y Guattari, Félix. (19949. Capitalismo y Esquizofrenia. Madrid: Mil Mesetas.Deleuze, Gilles. (1990). Conversaciones 1972-1990. París: Edición de Minuit.Duque Cañas, Juan. 2019. “La ranchería de los wayuu en la guajira”. Revista  Credencial, 15 de septiembre, URL:http://www.revistacredencial.com/credencial/historia/temas/la-rancheria-de-los-wayuu-en-la-guajiraDussel, Enrique. (19779. Filosofía Ética Latinoamericana. De la Erótica a la Pedagógica. México: Editorial EDICOL.Escobar, Arturo. (1999). El final del Salvaje. Naturaleza, Cultura y Política en la Antropología Contemporánea. Bogotá: Editorial Cerec.Escobar, Arturo. (2005). “Más allá del tercer mundo: globalidad imperial, colonialidad global y movimientos sociales anti-globalización”. Revista Nómadas 20: 86-100. Feminismo poscolonial.Foucault, Michel. (1968). Las palabras y las cosas. Una arqueología de las ciencias humanas. Buenos Aires: Siglo XXI Editores.Foucault, Michel. (1969). La arqueología del saber. Bogotá: Siglo XXI.Foucault, Michel. (1979). Microfísica del poder. España: Las Ediciones de La Piqueta.Foucault, Michel. (1984). El sujeto y el poder. Santiago de Chile: Escuela de Filosofía.Foucault, Michel. (1987). Hermenéutica del sujeto. Madrid: Ediciones de la Piqueta.Foucault, Michel. (1999). Estrategias del Poder. Barcelona: Ediciones Paídós Ibérica, S.A.Foucault, Michel. (2007). El nacimiento de la biopolítica. Curso del Collége de France 1978-1979. Buenos Aires: Fondo de Cultura Económica.García Canclini, Néstor. (2004). “Desiguales, Diferentes o Desconectados”. Revista CIDOB d’AfersInternacionals 66-67:113-133. Giraldo, Isaza Fabio. (2007). La globalización: Integración psíquica al mercado. En: Pánico en la Globalización, editado por Fabio Giraldo Isaza, 132-133. Cali: Editorial FICA.Guadarrama González, Pablo. (2016ª). Democracia y derechos humanos: visión humanista desde América Latina. 1 v. Bogotá: Taurus.Guadarrama González, Pablo. (2016b). Democracia y derechos humanos: visión humanista desde América Latina. 2 v. Bogotá: Taurus.Luhmann, Niklas. (2007). La sociedad de la sociedad. Ciudad de México: Editorial Herder S. de R.L. de C.V.Luxemburgo, Rosa. (1974). Introducción a la economía política. España: Siglo XXI, Colección Clásicos del pensamiento crítico.Maldonado, Carlos Eduardo. (1997). Ética y cultura latinoamericana. La ética de los derechos humanos. En: Pedagogía y derechos humanos: encuentros y desencuentros, compilado por Olga B. Gutiérrez T. y Fernando González S., 25-44. Bogotá: Editorial Red Latinoamericana de Educación para la paz y los derechos humanos.Maldonado, Carlos Eduardo. (2004). “Explicando la sorpresa. Un estudio sobre emergencia y complejidad”. En: Causalidad o emergencia. Diálogo entre filósofos y científicos, editado por Sociedad Colombiana de Filosofía de la Ciencia, 31-63. Bogotá: Editorial Universidad de la Sabana.Márquez Fernández, Álvaro. (2006). “Globalización neoliberal y crítica de la Filosofía intercultural”.  En: La Globalización indolente en América Latina, editado por Salazar Robinson, 59-102. Argentina: Editores Insumisos.Márquez Fernández, Álvaro. (2016). Prólogo. En: Políticas de la globalización: Organizaciones, Economía, Medio Ambiente, Cultura y Universida, editado por Katia Martínez Heredia, 13-16. Editorial Publicia. España: Editorial Publicia.Martínez Heredia, Katia Milena. (2013). “La educación política desde una perspectiva bio-política contemporánea”. Revista Reflexión Política 15-29: 34-43. Martínez Heredia, Katia Milena. 2015. Política de las Multitudes. Medios alternativos de comunicación en el contexto biopolítico contemporáneo. Saarbrücken: Editorial Académica Española.Martínez Heredia, Katia Milena. (2016). Políticas de la globalización: Organizaciones, Economía, Medio Ambiente, Cultura. Saarbrücken: Editorial Publicia.Morgan, Lewis H. (1877). Ancient Society. New York: Worl Publishing.Morin, Edgar. (2011). La vía para el futuro de la humanidad. Madrid: Editorial Paidós.Najmanovich, Denise. (2005). “La complejidad: de los paradigmas a las figuras del pensar”. COMPLEXUS Revista de Complejidad, Ciencia y Estética 1-2: 1-10. Negri, Toni y Hardt, Michael. (2000). Imperio. Barcelona: Ediciones Paidós. Ibérica S.A.Negri, Toni y Hardt, Michael. (2006). Multitud. Barcelona: Ediciones Paidós. Ibérica S.A.Negri, Toni. Hardt, Michael, Cocco, Giuseppe. Revel, Judith. García Linera, Álvaro y Tapia, Luis. (2007). Imperio, multitud y sociedad abigarrada. La Paz: Muela del Diablo Editores.Negri, Toni. Hardt, Michael. (2008). “El movimiento de los movimientos”. En: Imperio, multitud y sociedad abigarrado, editado por el Consejo Latinoamericano de Ciencias Sociales. La Paz: Muela del Diablo Editores.Rivera Cusicanqui, Silvia. (2019). En: El Salto El Diario. 17 de febrero de 2019. Silvia Rivera Cusicanqui: “Tenemos que producir pensamiento a partir de lo cotidiano”. https://www.elsaltodiario.com/feminismo-poscolonial/silvia-rivera-cusicanqui-producir-pensamiento-cotidiano-pensamiento-indigenaRivera Cusicanqui, Silvia. (2015).Sociología de la imagen: ensayos. 1a ed. - Ciudad Autónoma de Buenos Aires: Tinta Limón,Roig, Arturo Andrés. (2000). Ética del poder y moralidad de la protesta. La moral latinoamericana de la emergencia. Quito: Casa editorial: Universidad Andina Simón Bolívar / Corporación Editora Nacional.Ruggeri, Andrés; García Jané, Jordi y Iametti Señoriño, Ana. (2012). Autogestión y Economía Solidaria. Bilbao: Papeles de Economía Solidaria 3 de la Red de Economía Alternativa y Solidaria de Euskadi-REAS.Stiglitz, Joseph. (2002). “Whither reform? Towards a new agenda for Latin America”. Cepal Review 80: 7-37.Stiglitz, Joseph. (2004). Cómo hacer que la Globalización funcione.  Colombia: Editorial Taurus.Weber, Max. (1979). El político y el Científico. Madrid. Madrid: El libro de Bolsillo. Alianza Editorial.Zibechi, Raúl, (2008). Ecos del subsuelo: resistencia y política desde el sótano. De los saberes de la emancipación y de la dominación. Buenos Aires: CLACSO Editorial/Editor.